EIA in Malaysia : preliminary review on the implementation issues and challenges towards sustainable development / Nurulhuda Ali, Anuar Alias and Khairul Nizam Othman - Ali, Nurulhuda; Alias, Anuar; Othman, Khairul Nizam (2012)
Environmental Impact Assessment (EIA) has been an important tool in ensuring sustainable development. Malaysia has imposed the needs for EIA in the Environmental Quality Act (1974) for the property development process. However, issues of EIA process and implementation in Malaysia particularly in the context of property development still arose. Therefore, there are issues and challenges that need proactive and aggressive measures to overcome and rectify the current problems. .evertheless, there are still loopholes that can be further improved in order to ensure more efficient and effective EIA process and implementation as well as for EIA to meet its objectives. Thus, stakeholders' roles have been evaluated in the decision making process contexts which focus on the government agencies, project proponent and public. A face to face interview with stakeholders has been performed for analysis purpose. Recommendations for remedial and improvement of the implementation of EIA in Malaysia has been proposed which covers the administrative, implementation and legal aspects. The stakeholders should be committed to make sure EIA achieve its goals and environment is protected for the benefit of current and future generation towards sustainable development.